Pharmaceutical Analytical Study of Paribhdra Rasa and its Antifungal Study on Aspergillus Fumigatus and Candida Albicans - Vikas Chaudhary; Ravi Raj (AYUSHDHARA, 2025)
Rasashastra deals with the use of metals, minerals, gemstones, certain poisonous herbs and their processing. In Rasashastra, mercury is used as chief material and Rasaushadhis considered as more effective and beneficial due to lesser therapeutic doses, enhancement of action of other ingredients of formulation, more shelf life, quicker action and palatability as compared to herbal preparation. Rasaushadhis are being the backbone of Ayurveda due to its Rasayana and therapeutic properties. As the Paribhdra Rasa is mentioned in the Dadru Kustha. In Ayurveda, all skin diseases are categorized under the broad term Kushtha. Skin diseases in Ayurveda are further classified into Maha Kushtha and Kshudra Kushtha. Dadru is one type of Kushtha and known for its fast-spreading and invasiveness in nature. Dadru can be associated with fungal infections in modern science. Therefore “Pharmaceutical Analytical Study of Paribhdra Rasa and its Antifungal Study on Aspergillus Fumigatus and Candida Albicans” is chosen for present study.